On-site sewage treatment facilities, unacceptable quality or too small to count? : cost-benefit analysis of on-site sewage treatment facilities and the zeroeutrophication target - Gudinge, Philip (SLU/Dept. of Economics, 2017)
Private on-site sewage treatment facilities are only a small part of the Baltic Sea eutrophication problem, but it have caught attention due to its high share of deposition of nitrogen and phosphorus in comparison to the more efficient public sewage treatment plants. The treatment of sewage wastewater is regulated by the Swedish Environmental Code.